Avalia????o da qualidade assistencial de uma UTI adulto em um hospital p??blico da cidade de S??o Paulo por meio dos dom??nios: seguran??a, efetividade, efici??ncia e centralidade no paciente - Amorim, ??ngelo M??rio Vieira (2017)
Health is a complex system of service rendering, which has among its basic premises the search for quality and the guarantee of safety to users and patients. However, some hospital institutions have difficulty in diagnosing what should be implemented to meet these requirements. As a result, evaluate the level of health care provided in an ICU in public hospitals - through the domains of quality: safety, effectiveness, efficiency and centrality in the patients. The purpose of the present study was to analyze the quality and safety of patients in an adult intensive care unit (ICU) of a public hospital located in the city of S??o Paulo, and provides subsidies for the evaluation of their performance, enabling the institution to question its own results for decision making. As a methodological procedure, quality indicators related to the dimensions of safety, effectiveness, efficiency and centrality in the patient were surveyed, as well as the application of a questionnaire using sub-dimensions of patient safety assurance in 52 workers from different professional categories, who work on the unit searched. As results, it was possible to observe high rates of bloodstream infection associated with central venous catheters. In addition, with the use of analysis of variance (ANOVA), it was possible to identify that the variables associated with dimensions - management support and non-punitive responses - were the most relevant from the point of view of statistical significance (p> 0.05) as conditioners for a safe care to patient.